Undergraduate Learning in the COVID-19 Pandemic: Lessons Learned and Ways Forward - Kajjimu, Jonathan; Dreifuss, Heather; Tagg, Andrew; Dreifuss, Bradley; Bongomin, Felix (Advances in Medical Education and Practice, 2023)
The SARS-CoV-2 coronavirus (COVID-19) pandemic is in constant evolution, much like the virus, and we must learn to adapt our undergraduate education and learning strategies to enable students to complete their studies. This narrative review focuses on what is currently known about the face-to-face and e-learning strategies of undergraduate medical students in resource-limited settings during the COVID-19 pandemic. The majority of studies, involving health professional students, took place in 2020. Few involved educators. Students have faced challenges with the transition to remote learning, for which a couple of interventions have been devised. Bridging the gap in access and utilisation of remote learning might have required more time, however, the COVID-19 pandemic has accelerated the learning curve and the transition from in-person to online learning.
Keywords: Undergraduates; Physical learning; E-learning; COVID-19; Digital learning; Online learning; Face-to-face learning; Traditional learning; Remote learning; Virtual learning